2023
DOI: 10.1590/1519-6984.244977
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of active HCV infection and genotypic distribution among the general population of district Mardan, Pakistan

Abstract: Hepatitis C virus (HCV) is the serious global public health burden of liver disease. Approximately 170 million people in the world are infected with (HCV). In Pakistan, where the disease has high occurrence rate. The present study envisages an up-to-date prevalence of HCV and genotypic distribution in the general population of Mardan District, Khyber Pakhtunkhwa (KP), Pakistan. The blood samples from 6,538 individuals including 3,263 males and 3,275 females were analyzed for hepatitis C surface antigen by Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…Data analysis demonstrated that the HCV genotype 3 was more frequent in females (70.8%) than in males (68.9%). These results are in compliance with the outcomes of previous studies conducted in different regions of the country, which also indicated HCV 3 genotype to be the most prevalent genotype reported [16]. Other Asian countries (e.g., India and Nepal) also showed a similar prevalence pattern with a higher frequency of HCV genotype 3 [17], whereas South Asian Countries (e.g., Vietnam, Thailand, and Japan) indicated a different pattern with HCV genotype 1a being the most prevalent genotype [18].…”
Section: Discussionsupporting
confidence: 92%
“…Data analysis demonstrated that the HCV genotype 3 was more frequent in females (70.8%) than in males (68.9%). These results are in compliance with the outcomes of previous studies conducted in different regions of the country, which also indicated HCV 3 genotype to be the most prevalent genotype reported [16]. Other Asian countries (e.g., India and Nepal) also showed a similar prevalence pattern with a higher frequency of HCV genotype 3 [17], whereas South Asian Countries (e.g., Vietnam, Thailand, and Japan) indicated a different pattern with HCV genotype 1a being the most prevalent genotype [18].…”
Section: Discussionsupporting
confidence: 92%
“…Ahora bien, en la epidemiologia de las enfermedades hepáticas del adulto mayor se evidenció una prevalencia en el virus de hepatitis B, sin embargo, en un estudio realizado en Colombia por Rojas y col. (Rojas et al, 2018) mencionan que entre las complicaciones frecuentes de las infecciones crónicas de la cirrosis fue causada por el virus de hepatitis C, teniendo una prevalencia del 29,4%, evidenciando la susceptibilidad de la población estudiada para la En cuanto a la incidencia, según los resultados obtenidos el carcinoma hepatocelular se destacó entre los estudios escogidos con 56,3%, a diferencia de otros estudios que se efectuaron, entre ellos Ullah y col. (Ullah et al, 2020) realizaron un estudio en China y mencionan que en el género masculino en un rango de 60-70 años tuvo un 1, 04% de hepatitis C. Se evidenció que la incidencia varia en el origen de la hepatopatía y el predominio en el género masculino en base a los estudios encontrados.…”
Section: Discussionunclassified
“…En referencia a la mortalidad, la cirrosis hepática presenta una elevada incidencia en cuento a los estudios identificados, pero en una investigación realizada por Viera y col. (Viera-Santillan et al, 2018) en Perú evidencian una frecuencia de mortalidad del 21,2% en pacientes cirróticos, y menciona que la ascitis es un factor asociado. Por otra parte, en Brasil Ferro y col. (Ferro-Cavalcante et al, 2022) encontraron que el 26,3% de las muertes del carcinoma hepatocelular estuvieron asociados a la hepatitis B o C.…”
Section: Discussionunclassified
“…One more study observed that the RNA genome showed significant heterogenetic variations with nucleotide interchange values of 1.44 × 10 −3 and 1.92 × 10 −3 per position annually [21] . Genetic variability of HCV isolates consists of 4 levels the first one is types with 65.7%–8.9% nucleotide sequence, the second one is subtypes with 76.9%–80.1% nucleotide sequence, the third and fourth is isolates and quasispecies with 90.8%–99% nucleotide sequence.…”
Section: Molecular Evolution Of Hcvmentioning
confidence: 99%